Rhodanineacetic Acid Derivatives as Potential Drugs: Preparation, Hydrophobic Properties and Antifungal Activity of (5-Arylalkylidene-4-oxo-2-thioxo-1,3-thiazolidin-3-yl)acetic Acids - Josef Jampilek; Jiri Kunes; Vejsova Marcela; Petra Hirsova; Jiri Dohnal; Veronika Opletalova; Jan Dolezel (Molecules, 2009)
Some [(5Z)-(5-arylalkylidene-4-oxo-2-thioxo-1,3-thiazolidin-3-yl)]acetic acids were prepared as potential antifungal compounds. The general synthetic approach to all synthesized compounds is presented. Lipophilicity of all the discussed rhodanine-3-acetic acid derivatives was analyzed using a reversed phase high performance liquid chromatography (RP-HPLC) method. The procedure was performed under isocratic conditions with methanol as an organic modifier in the mobile phase using an end-capped non-polar C18 stationary RP column. The RP-HPLC retention parameter log k (the logarithm of the capacity factor k) is compared with log P values calculated in silico. All compounds were evaluated for antifungal effects against selected fungal species. Most compounds exhibited no interesting activity, and only {(5Z)-[4-oxo-5-(pyridin-2- ylmethylidene)-2-thioxo-1,3-thiazolidin-3-yl]}acetic acid strongly inhibited the growth of Candida tropicalis 156, Candida krusei E 28, Candida glabrata 20/I and Trichosporon asahii 1188.